Les représentations conceptuelles de l'estime de soi et de la motivation chez les enseignants spécialisés - Basma Frangieh; Nathalie Gavens (Nantes Université, 2015)
This article discusses the support that a training programme based on discussions of key concepts such as self-esteem and motivation can bring to special teacher's practices. The objective of this study is to collect and discuss the conceptual representations that special teachers following a certifying training programme have of these concepts. The research was conducted in three stages: the collection of initial conceptual representations, discussions about these conceptual representations, and finally the educational actions that can be implemented in the classroom to develop feelings of motivation and self-esteem among impaired students. Our findings indicate that enlightening professionals about their representations enables them to be more effective in their educational practice.